Who brings more gender equality in couple’s time use in Hong Kong—co-resident elderly parents or helpers? - Chen, M; Zhou, M (Taylor and Francis, 2021)
In Hong Kong, extended households are declining while households with helpers are increasing. More and more couples resort to hiring helpers instead of living with elderly parents to outsource domestic work. Currently, it is not clear whether elderly parents and helpers would have the same impact on couples’ time use. To fill this gap, the study examines couples’ paid work time and domestic work time, as well as the gender gap in time use in different household types (i.e. couple-only households, households with elderly parents, and households with helpers). It uses the couple data from the first wave of Hong Kong Panel Study of Social Dynamics in 2011 and conducts the inverse propensity weighting with regression adjustment (IPWRA) analysis. The results show that couples’ total domestic work is reduced to a greater extent in the helper household than that in the elderly-parent household. But this difference disappears if couples live with relatively younger, healthy, and retired parents. Although the impact of younger, healthy, and retired parents and hired helpers would reduce couples’ total domestic work time similarly, they are different in the sense of “help for whom”: hired helpers reduce the gender gap in paid work time and domestic work time, mainly by influencing wives’ time use; elderly parents reduce couples’ domestic work time in a less gendered way, favoring both husbands and wives. Elderly parents and helpers could reduce couples’ domestic workload more or less, but whether gender equality is promoted through outsourcing is worth more attention.